Does Use of Different Platforms Influence the Relationship between Cocreation Value-in-Use and Participants’ Cocreation Behaviors? An Application in Third-Party Managed Virtual Communities - Natalia Rubio; Nieves Villaseñor; Maria Jesús Yague (Complexity)
Despite an increasing amount of research on cocreation value, research on participants’ value-in-use in third-party managed virtual communities remains limited. This study explores how participants perceive value-in-use through their participation in third-party managed virtual communities and the influence of the participants’ value-in-use on three cocreation behaviors typical of these communities: information searching, feedback, and coinnovation activities. Participant value-in-use is a multidimensional construct consisting of five dimensions: informational value, entertainment value, social integrative value, personal integrative value, and community interactivity. We also consider whether use of different platforms (website, mobile app, or both) exerts a moderating effect on this cocreation process and identify significant differences in the relationships proposed based on the platform the participants use to access the virtual community. The research is contrasted empirically using the virtual community TripAdvisor. The PLS-SEM method is used to test the model proposed. In comparing the website and mobile app models, the results show significantly stronger effects on the relationships in the route “informational value-participants’ value-in-use-information searching” for the website. Also, we find a stronger route for personal integrative value-participants’ value-in-use-feedback among users of the mobile app than for website users. In the case of participants who use only one platform (website or mobile app) rather than both (website and mobile app), the weight of use of one technology rather than both is significantly greater in coinnovation. This study enriches previous studies that advance theories of cocreation value and provides companies with practical guidance to identify and encourage cocreation behaviors and enhance the perceived value-in-use of virtual community participants.